Women, Peace and Security National Action Plans in anti-gender governments: The cases of Brazil and Poland. (November 2022) - Thomson, Jennifer; Whiting, Sophie
Abstract: In recent years, Brazil and Poland have elected governments that are sceptical of both the liberal international order and gender. In both cases, contemporary administrations have bolstered the pre-existing anti-gender offensive of religious and secular conservative forces and converted this into legislation and public policy. Yet, at the same time, both have also created National Action Plans around the UN's Women, Peace and Security agenda. Why is this the case? Why do two governments that see gender as an 'ideology' continue to work on WPS? Using a feminist institutionalist framework, this article draws on content analysis of the NAPs and semi-structured in-depth interviews with stakeholders in Brazil and Poland to explore this puzzle. We argue that the WPS agenda has survived in these political contexts due the presence of key 'femocrats' within the state; the influence of international institutions; and the symbolic power that the WPS agenda gives to these countries on the world stage. As such, the article makes a key contribution to the literature on the WPS agenda and also bolsters the argument for a complication of the idea of gender 'backlash' – in domestic and international audiences, states are willing to adopt different attitudes to gender if it furthers their interests.